Pathophysiology of Primary Headache Syndrome: A Narrative Literature Review - Asmedi, Ahmad (Phlox Institute: Indonesian Medical Research Organization, 2023)
Primary headache syndrome is a chronic recurrent type not associated with structural abnormalities or systemic disease and includes migraine, cluster, paroxysmal hemicrania, and tension headaches. This literature review aimed to describe the types of primary headaches and their pathophysiology. Migraine is an episodic neurological disorder characterized by headaches that last 4 to 72 hours. This disorder is diagnosed when two of the following features occur: unilateral headache, throbbing pain, the pain worsening with activity, moderate or severe pain intensity, and at least one of the following: nausea and/or vomiting, or photophobia and phonophobia. Cluster headaches are one of a group of rare disorders known as trigeminal autonomic cephalgia. Tension-type headache (TTH) is the most common type of recurring headache. It's not a vascular headache or a migraine. The mean age of onset is during the second decade of life. Usually mild to moderate bilateral headaches with a feeling of tight bands or pressure around the head.